An applications development for record keeping of police stations in Pakistan - Shah, Abdul Salam; Fayaz, Muhammad; Shah, Asadullah; Shah, Shahnawaz (Journal of Scientifc Research and Advances, 2015)
The police and Police stations have its adequate importance all around the world in this era where the crime rate is very high, stations of Pakistan is also same. Currently, the police stations in Pakistan are utilizing the old method ( hard paper) of FIR registrations and which require extra efforts to maintain the record of criminals and trace someone;s record also require unnecessary time which can be saved by digitizing the police stations records. Although, some police stations do use digital record keeping in Excel sheets but the integrity problem is noticed in file based record also the access is slower for searching single record the officer.official has to go through all the records in the sheet which consumes extra time. The Excel sheets can only be used by a single person at a time and also they do not have any security mechanism, anyone who has access to the computer can easily access the sensitive record. To overcome these issues we have developed an applications for the police station to digitize the method of FIR system and other important official records about the staff and necessary registers used by police stations.